THE EFFECT OF CROSSFIT EXERCISES ON THE MAXIMUM ANAEROBIC CAPACITY OF YOUNG FOOTBALL PLAYERS - Asst. Prof. Dr. Abdullah Mohammed Tayawi; Dr. Adnan Mohammed Shanawa (Scholars Digest Publishing, 2024)
The study aimed to explore the effect of CrossFit training on the maximum anaerobic capacity of young football players. Specifically, it sought to: 1. Assess the results of the pre- and post-tests of maximum anaerobic capacity for the experimental and control groups. 2. Compare the differences in the post-test results of maximum anaerobic capacity between the two groups. The most important conclusions indicate that competitive exercises combined with CrossFit training, implemented through high-intensity interval training, had a positive impact on the maximum anaerobic capacity of young football players. Furthermore, CrossFit training using high-intensity intervals positively influenced the research variable among these players. The research population and sample were selected from the Al-Alam Football Club, which participated in the first youth league for the 2021-2022 season. The number of registered players, according to the Salahuddin Football Association, was thirty-two. After conducting medical examinations, including echocardiograms (Echo) to ensure the cardiac fitness of the players, and clinical tests by a specialist in cardiology and internal medicine to confirm their health status, the researchers divided the sample into two groups (experimental and control). The division was done by matching players based on their measurements, capabilities, and positions, as much as possible, and a lottery was conducted. Each group consisted of twelve players, after excluding eight players (3 goalkeepers, one player with mitral valve prolapses as advised by the doctor, and four players due to injuries or irregular attendance in training).
Keywords: International Accounting Standards, Quality of Financial Reporting, Commercial Banking.